Green Open Space Quality and Citizen Satisfaction in Public Service Delivery in Bandung: The Role of Psychological Comfort and Pro-Environmental Attitude - Rachmat, Rachmat; Johan, Ahmad (Jurnal Manajemen Pelayanan Publik, 2026)
Green open spaces (Ruang Terbuka Hijau/RTH) represent a critical form of urban public service infrastructure that contributes to citizen well-being and urban sustainability. Despite their importance, limited empirical attention has been given to understanding the mechanisms through which citizens evaluate the quality of these public spaces and form satisfaction judgments, particularly in the Indonesian urban context. Drawing on the Stimulus-Organism-Response (S-O-R) framework, this study examines how perceived RTH quality influences citizen satisfaction, focusing on the mediating role of psychological comfort and the moderating role of pro-environmental attitude. Data were collected from 200 residents of Bandung, West Java, using purposive online sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived RTH quality is positively associated with citizen satisfaction, both directly and indirectly through psychological comfort. Furthermore, the relationships between RTH quality and both psychological comfort and satisfaction are stronger among citizens with higher pro-environmental attitudes. These findings contribute to the public service and urban management literature by elucidating the experiential and attitudinal mechanisms underlying citizen satisfaction with green public infrastructure. Practical implications for municipal RTH management, including maintenance, accessibility, and citizen engagement strategies, are discussed.